Private Investment in Water and Sewerage Recovers in 2011, Mostly Due to Activity in China - Militaru, Andreea (World Bank, Washington, DC, 2014)
In 2011, 31 new water and sewerage projects reached financial or contractual closure in six lower-and upper-middle income countries: Algeria (1), Brazil (2), China (26), Jordan (1), Mexico (1) and Peru (1). Total investment commitments in water projects reached US$2.6.2 billion, of which over US$1 billion included investments in existing projects and US$1.5 billion included investments in new projects. Compared to 2010, private activity by number of projects increased by 24 percent, while by total investment it increased by 8.3 percent.